Fluorine Etching in Porous Silicon: An Ab-Initio Molecular Dynamics Study. (1st January 2017) - Arcos, Marisol R.; Wang, Chumin
Abstract : Surface atom removal by fluorine in porous silicon is studied by using the first-principles molecular dynamics based on the density functional theory. The results confirm the preferential <100> crystalline etching direction, in agreement with the experimental results. Moreover, surface silicon atoms are mostly captured by two fluorine and two hydrogen atoms, producing difluorosilane (SiH2 F2 ), in contrast to the widely accepted four fluorine-atom capture model. This new capture process could be verified by the infrared spectroscopy.